2020
DOI: 10.1186/s12974-020-01765-w
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of intrathecal injection of miR-9-5p modified mouse bone marrow mesenchymal stem cells on a mouse model of bone cancer pain

Abstract: Background: A growing body of studies have indicated that bone marrow mesenchymal stem cells (BMSCs) have powerful analgesic effects in animal models of bone cancer pain. Here, we explored the molecular mechanisms underlying how BMSCs alleviate pain sensation in a mouse model of bone cancer pain.Methods: C3H/HeN adult male mice were used to generate a bone cancer pain model. BMSCs were isolated from mouse bone marrow, modified by transfection with microRNA-9-5p (miR-9-5p), and infused into the spinal cord. Spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Reports showed the inhibitory roles of miR-105-5p in the proliferation and migration of glioma cells, while the regulatory mechanism during the process is still undefined 36,37 . Previous studies have found that miR-9-5p could interact with REST and regulate its gene expression 38,39 . Taken together, miR-9-5p and miR-105-5p/REST axis were identified as potential regulatory pathways in glioma, representing a novel potential treatment strategy for glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Reports showed the inhibitory roles of miR-105-5p in the proliferation and migration of glioma cells, while the regulatory mechanism during the process is still undefined 36,37 . Previous studies have found that miR-9-5p could interact with REST and regulate its gene expression 38,39 . Taken together, miR-9-5p and miR-105-5p/REST axis were identified as potential regulatory pathways in glioma, representing a novel potential treatment strategy for glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Direct linkage of miR-9, in Schwann cells or otherwise, to pain phenotypes remains understudied. An anti-nociceptive effect from intrathecal administration of miR-9 overexpressing bone marrow mesenchymal stem cells, and consequent reduction in spinal cord neuroinflammatory readouts, has been reported in a mouse model of bone cancer pain (C. Zhu et al, 2020 ).…”
Section: Ncrnas In Schwann Cell Responses Following Nerve Injurymentioning
confidence: 99%
“…Our previous study showed that transplantation of olfactory ensheathing cells (a type of glial cell similar to SCs) also had a pain‐relieving effect (Zhang et al, 2019; Zhang, Luo, Zhu, et al, 2020). Transplantation of other cells such as chromaffin cells and mesenchymal stem cells may relieve intractable cancer‐induced pain (Lazorthes et al, 1995; Zhu, Wang, et al, 2020). A recent clinical trial found that autologous SCs were injected into two patients with spinal cord injury; one patient's motor function improved by four points, sensory function improved by six points, and the level of nerve injury improved by one point.…”
Section: Scs and Cancer Pain Treatmentmentioning
confidence: 99%